Design of programmable coiled-coil protein nanostructures for bioengineering applications - Mahmoud, Mohamad (My University, 2026)
Coiled coils comprise two or more α-helices wrapped into a superhelix. They are characterized by a heptad repeat pattern of hydrophobic and polar amino acid residues that governs their stability and specificity. Their remarkable biophysical features, including high binding affinity, interaction specificity, and structural stability, render coiled coils attractive for the design of self-assembled protein nanomaterials, as widely observed in fibrous proteins and highly ordered self-assembled architectures. However, the rational design of programmable protein assemblies with controlled properties remains a significant challenge. Addressing this limitation is critical for applications in bioengineering. In this study, we designed coiled-coil-based building blocks to generate two distinct classes of protein nanomaterials: amphiphilic nanobundles and orthogonally interacting helical binders. These systems offer versatile and modular platforms for diverse bioengineering applications. The first project focuses on the computational design of amphiphilic protein nanobundles. We integrated the interfacial properties of class II hydrophobins, HFBI, and the oligomerization capabilities of a hexameric coiled-coil bundle, HexCC, via genetic fusion. Linker sequences between the HexCC and HFBI domains were computationally screened, and a single glycine residue was identified as the optimal linker based on the evaluation of predicted protein structures. The stability of the designed protein nanobundles, HFBI-HexCC and HFBIAV-HexCC, was further supported by normal mode analysis and molecular dynamics simulations. Both proteins were successfully expressed in and purified from Escherichia coli cultures, where structural and biophysical characterization confirmed the formation of nanobundles that self-assembled on hydrophobic plastic substrates such as polytetrafluoroethylene. The protein-coated surfaces exhibited significantly reduced protein adsorption and bacterial adhesion, demonstrating their potential as antifouling biomaterials. To further enhance functionality, the antimicrobial peptide thanatin (THA) was genetically fused to HFBI-HexCC, resulting in suppression of E. coli growth. These results demonstrate the potential of HFBI-HexCC as a versatile platform for antifouling biomaterial coatings. The second project focuses on designing orthogonal, asymmetric helical heterodimers with reduced promiscuous binding to enable programmable coiled-coil protein origami. Our design strategy was based on previously designed coiled-coil homodimers with modular networks of hydrogen bonds between their four-helix bundles. The linker loop connecting the two helices in the parent homodimer was relocated to generate asymmetric interaction pairs comprising a single helix and a triple-helix binder. Candidate pairs were screened using AlphaFold3, leading to the identification of three orthogonal pairs. These hydrogen-bond-mediated asymmetric binders were termed HyZips. Orthogonality was experimentally evaluated both in vitro and in vivo using a split luciferase complementation assay in which the HyZip2h-2b0 and HyZip3h-3b3 exhibited strong cognate interaction with minimal crosstalk. MD simulations further confirmed the preservation of the designed conformation and hydrogen-bond networks. These results show that hydrogen-bond networks can be engineered into proteins to achieve programmable specificity in protein-protein interactions, providing a versatile set of interaction modules for synthetic biology applications. Overall, this work demonstrates how coiled-coil proteins can be rationally engineered into self-assembling nanostructures with programmable structures, properties, and functions. By establishing design principles that govern intermolecular interactions, interfacial orientation, and functional domain integration, these studies expand the toolkits for creating functional protein nanomaterials and orthogonal interaction networks. The versatility and robustness of these engineered coiled-coil systems, along with design principles established herein, provide new opportunities for biomaterial engineering, protein origami, and synthetic biology.
Keywords: Coiled-coil proteins; Protein origami; Amphiphilicity; Orthogonal interactions; Bioengineering; Synthetic biology